New genetic signatures associated with cancer cachexia as defined by low skeletal muscle index and weight loss. Issue 1 (5th August 2016) - Johns, Neil; Stretch, Cynthia; Tan, Benjamin H.L.; Solheim, Tora S.; Sørhaug, Sveinung; Stephens, Nathan A.; Gioulbasanis, Ioannis; Skipworth, Richard J.E.; Deans, D.A. Christopher; Vigano, Antonio; Ross, James A.; Bathe, Oliver F.; et al.
Abstract : Background: Cachexia affects the majority with advanced cancer. Based on current demographic and clinical factors, it is not possible to predict who will develop cachexia or not. Such variation may, in part, be due to genotype. It has recently been proposed to extend the diagnostic criteria for cachexia to include a direct measure of low skeletal muscle index (LSMI) in addition to weight loss (WL). We aimed to explore our panel of candidate single nucleotide polymorphism (SNPs) for association with WL +/− computerized tomography‐defined LSMI. We also explored whether the transcription in muscle of identified genes was altered according to such cachexia phenotype Methods: A retrospective cohort study design was used. Analysis explored associations of candidate SNPs with WL ( n = 1276) and WL + LSMI ( n = 943). Human muscle transcriptome ( n = 134) was analysed using an Agilent platform. Results: Single nucleotide polymorphisms in the following genes showed association with WL alone: GCKR, LEPR, SELP, ACVR2B, TLR4, FOXO3, IGF1, CPN1, APOE, FOXO1, and GHRL. SNPs in LEPR, ACVR2B, TNF, and ACE were associated with concurrent WL + LSMI. There was concordance between muscle‐specific expression for ACVR2B, FOXO1 and 3, LEPR, GCKR, and TLR4 genes and LSMI and/or WL ( P < 0.05). Conclusions: The rs1799964 in the TNF gene and rs4291 in the ACE gene are new associations when the definition of cachexia is based on a combination of WL and LSMI. These findings focus attention on pro‐inflammatory cytokines and the renin–angiotensin system as biomarkers/mediators of muscle wasting in cachexia.